Fish Feed Formulation with the Addition of Sludge of Dairy Wastewater and Fermented Wheat Bran - Widya Pangestika; Sugili Putra (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
HighlightColloids in dairy wastewater could be destabilized by adding ferric chlorideAspergillus niger could increase protein and decreased the crude fiber in wheat branWheat bran fermentation could be carried out in room temperature during three daysFish feed formulation was conducted by solving simultaneous linear equationsSludge of dairy wastewater and fermented wheat bran could be utilized as fish feedAbstractDairy wastewater contains suspended solids, which are very difficult to settle naturally. This waste could be treated by using ferric chloride, due to its ability to bind suspended solid and to form brown solid of Iron (III) hydroxide. The optimal amount of FeCl3 in coagulating dairy wastewater was 0.15 g of FeCl3 for every 250 mL of wastewater. This sludge could be utilized into something useful for the organism. The sludge of dairy wastewater could be mixed with other ingredients to make fish feed. Wheat bran, one of the ingredients used to make fish feed, was fermented using Aspergillus niger to increase the crude protein content and to lower crude fiber content. The addition of fermented wheat bran in fish feed formulation could increase the crude protein content in feed B (which had 0.085% iron) by 5.78% and feed C (which had 1.703% iron) by 5.17%. By using simultaneous linear equations, fish feed formulation was conducted by adding sludge of dairy wastewater, fermented wheat bran, rebon flour, starch, and vitamin C. In this research, two variations of fish feeds were made (feed B and feed C). The results indicated that feed B and feed C had better stability and buoyancy than feed A, as the commercial feed. Feed C also had the biggest crude protein of all feeds, amounting to 32.057%. Feed C also gave the best result in increasing nile tilapia's growth rate. The result showed that sludge of dairy wastewater and fermented wheat bran could be added to fish feed formulation.